The Influence of Influencers and Social Media as Promotional Media on the Interest in Visiting the Lok Baintan Floating Market - Putri Nor Amelya; Isra Ul Huda; Tina Lestari (Green Publisher Indonesia, 2024)
This study aims to determine the relationship and how much influence between Influencers and Social Media on Visiting Interest in the Lok Baintan Floating Market. The population in this study were Nusantara visitors in 2023 and a sample of 100 respondents. Data was collected using a questionnaire and analyzed by multiple linear regression using spss027 for window. The results showed that simultaneously the Influencer and Social Media variables had a significant effect on visiting interest in the Lok Baintan Floating Market. Partially, the Influencer variable has a significant effect on visiting interest in the Lok Baintan Floating Market while the Social Media variable has no significant effect on visiting interest in the Lok Baintan Floating Market. simultaneously the Influencer and Social Media variables affect the Interest in Visiting the Lok Baintan Floating Market. Influencer is an independent variable that has a dominant effect on Interest in Visiting the Lok Baintan Floating Market.